Citizenship Ecological in Citizenship Education: Strengthening Awareness Environment in Secondary Education - Vinna Dinda Kemala; Ryan Taufika; Nadziroh; Vinni Dini Pratiwi; Alil Rinenggo (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to explore the process of integrating ecological citizenship into Civic Education (PKn) learning in secondary schools, as well as identifying its impacts, challenges, and implementation strategies within the context of the Kurikulum Merdeka. Using a qualitative approach with a single-case study design, this study was conducted in a high school in Medan City with Adiwiyata status. Data were collected through multi-source techniques including in-depth semi-structured interviews with Civic Education teachers and the principal, non-interventional participant observation during six class sessions, critical analysis of curriculum documents, and three student Focus Group Discussions (FGDs). All qualitative data were analyzed interactively using the Miles, Huberman, and Saldaña model with open and axial coding techniques. The results showed that the integration of ecological citizenship through active-participatory strategies, the